Consumerism in world history : the global transformation of desire - Stearns, Peter N. (Themes in world history, 2001)
Machine generated contents note: Preface ix -- Acknowledgments xii --1 Before consumerism 1 --PART I : The emergence of consumerism in the West 13 -- 2 The emergence of consumerism 15 -- 3 The first causes of consumerism 25 -- 4 Consumerism across the Atlantic: an early imitation 37 -- 5 The explosion of consumerism in Western Europe and the United States 44 -- 6 The dark side of Western consumerism 61 --PART II : Consumerism goes global 73 -- 7 Consumerism in Russia 75 -- 8 Consumerism in East Asia 83 -- 9 Consumerism in Africa 101 -- 10 Consumerism in the Islamic Middle East 112 -- PART III : Consumerism toward the new century 123 -- 11 Consumerism in the contemporary world 125 -- 12 Conclusion: who wins - consumerism or consumers? 137 --Index 143